(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
Stryphnodendron adstringens (Mart.) Coville (barbatimão) is a tree belonging to the Fabaceae family, and it is commonly found in the southeastern Brazilian cerrado. The stem bark of this tree is traditionally used as an anti-inflammatory and antiseptic agent to treat leucorrhea and diarrhea, as well as to promote wound healing (owing to the presence of proanthocyanidins). Proanthocyanidins were obtained from the ethanolic extract of S. adstringens stem bark and assessed by reversed phase-high performance liquid chromatography with an ultraviolet/diode array detector. The identified compounds included gallic acid, catechin, gallocatechin (GC), epigallocatechin, and epigallocatechin gallate (EGCG). The selected markers, GC and EGCG, were simultaneously used for chromatographic validation (linearity range: 30-330 ng, equivalent to 3-33 µg/mL; r>;0.998). The method showed precision (intra-day relative standard deviation [RSD]: 1.72% for GC; 1.16% for EGCG; inter-day RSD: 1.74%-2.60% for both markers), accuracy, robustness, and selectivity. The limits of detection and quantitation were 0.29 µg/ml and 0.89 µg/ml for GC, and 0.88 µg/mL and 2.67 µg/mL for EGCG, respectively. In addition, S. obovatum was evaluated and showed an average of 12.2 µg/mL for GC (equivalent to 1.22% w/w) and 14.2 µg/mL for EGCG (equivalent to 1.42% w/w) in the ethanolic extract. The quantitative results were compared to those obtained for S. adstringens, which showed that the markers are present in both species.